2004
DOI: 10.1186/1743-0003-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Motor rehabilitation using virtual reality

Abstract: Virtual Reality (VR) provides a unique medium suited to the achievement of several requirements for effective rehabilitation intervention. Specifically, therapy can be provided within a functional, purposeful and motivating context. Many VR applications present opportunities for individuals to participate in experiences, which are engaging and rewarding. In addition to the value of the rehabilitation experience for the user, both therapists and users benefit from the ability to readily grade and document the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
159
0
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(177 citation statements)
references
References 38 publications
3
159
0
15
Order By: Relevance
“…A number of factors are thought to enhance plasticity-based rehabilitation, such as task-oriented movement practice in a challenging, engaging, functional, and meaningful way, and the rehabilitation should address body function and structures, activity, and participation level [9][10][11][12][13]15]. Rehabilitation has shown that, even in chronic stroke, improved upperlimb outcomes can be achieved [16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors are thought to enhance plasticity-based rehabilitation, such as task-oriented movement practice in a challenging, engaging, functional, and meaningful way, and the rehabilitation should address body function and structures, activity, and participation level [9][10][11][12][13]15]. Rehabilitation has shown that, even in chronic stroke, improved upperlimb outcomes can be achieved [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Movement practice and repetition form the basis of plasticity-based motor recovery [10][11][12][13][14]. A number of factors are thought to enhance plasticity-based rehabilitation, such as task-oriented movement practice in a challenging, engaging, functional, and meaningful way, and the rehabilitation should address body function and structures, activity, and participation level [9][10][11][12][13]15].…”
Section: Introductionmentioning
confidence: 99%
“…Computer-assisted technology, such as virtual reality, is considered a useful addition to rehabilitation because it offers a potential medium by which these key aspects can be provided [13][14][15]. In virtual reality, the user experiences a simulated "real" environment using dedicated computer software [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Estes achados tambĂ©m foram documentados em vĂĄrios estudos 3,7,19,20 . O motivo da melhora poderĂĄ ser explicado pelo processo de plasticidade cerebral, no qual o sistema vestibular habituou em decorrĂȘncia a uma resposta repetida dos exercĂ­cios propostos 12 A falta de movimentação corporal e o medo de sentir tontura faz com que o paciente restrinja seus movimentos corporais e, com isso, adquira maus hĂĄbitos posturais e, consequentemente, tensĂŁo da musculatura cervical para evitar o reaparecimento da tontura [23][24][25] .…”
Section: Discussionunclassified
“…Um dos recursos que vem sendo aplicado para o tratamento de reabilitação do sistema vestibular Ă© a realidade virtual, que utiliza estĂ­mulos que simulam situaçÔes da vida real 7,8 . É constituĂ­do por um emissor de imagens virtuais que recriam situaçÔes que causam tontura, propiciando compensação dos distĂșrbios vestibulares 9,10 .…”
Section: Introductionunclassified